Chaos-Based Image Encryption Algorithm Using Decomposition - Hongyao Deng; Xiuli Song (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The proposed chaos-based image encryption algorithm consists of four stages: decomposition, shuffle, diffusion and combination. Decomposition is that an original image is decomposed to components according to some rule. The purpose of the shuffle is to mask original organization of the pixels of the image, and the diffusion is to change their values. Combination is not necessary in the sender. To improve the efficiency, the parallel architecture is taken to process the shuffle and diffusion. To enhance the security of the algorithm, firstly, a permutation of the labels is designed. Secondly, two Logistic maps are used in diffusion stage to encrypt the components. One map encrypts the odd rows of the component and another map encrypts the even rows. Experiment results and security analysis demonstrate that the encryption algorithm not only is robust and flexible, but also can withstand common attacks such as statistical attacks and differential attacks. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3018